ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI CLASSICAL MUSIC THERAPY (BEETHOVEN) TERHADAP TINGKAT KECEMASAN PASIEN HEMODIALISA DI RSPAD GATOT SOEBROTO - Ega Rakha Alvita Deli (2023)
Patients on long-term hemodialysis are concerned about the uncertainty of their illness, the duration of hemodialysis, and chronic pain, which lead to frustration and anxiety. One way to overcome anxiety is to provide peace through classical music therapy (Beethoven). Classical music therapy (Beethoven) is an alternative therapy that increases comfort and reduces anxiety because it produces nitric oxide (NO) which can reduce anxiety. The purpose of implementing this care is to ensure the effectiveness of classical music therapy in reducing anxiety levels in hemodialysis patients. The patient's anxiety level was measured using the HARS questionnaire. Hemodialysis patients with a total HARS score greater than 14 received classical music therapy for 15 minutes before starting hemodialysis. The results found by nurses after providing classical music therapy (Beethoven) intervention were significant changes in the patient's anxiety level before being given intervention with a total HARS score of 20 and after being given an intervention with a total HARS score of 10. Therefore, it can be concluded that classical music therapy (Beethoven) is effective in reducing the anxiety level of hemodialysis patients. Keywords: Classical music therapy (Beethoven), anxiety, hemodialysis